Radionuclide Patterns of Ischemia in Acute Occlusive Diseases of Main Arteries of Lower Extremities - N. Y. Kudryashova; O. G. Sinyakova; I. P. Mikhaylov; E. V. Migunova; O. V. Leshchinskaya (Неотложная медицинская помощь, 2019)
Relevance The problem of diagnosing and treating patients with acute ischemia of the extremities against the background of thrombosis and atherosclerotic lesions of the main arteries remains very complex task and requires the use of various diagnostic methods, and the leading one is radiation diagnostics.The aim of the study . The development of radionuclide patterns of acute lower limb ischemia and assessment of the treatment efficacy in angiosurgical patients using three-phase scintigraphy. Material and methods The radionuclide method was performed to examine 264 patients with acute thrombosis of the main arteries against the background of atherosclerotic lesions of the lower extremities arteries and clinical signs of acute ischemia of the lower extremities of I-III degree according to the classification of I.I. Zatevakhin.Results We defined quantitative and visual signs of acute ischemia, designed radionuclide semiotics, which allowed to detail the damaged tissue of lower extremities and evaluate the efficacy of the conservative or surgical treatment. The study contains clinical examples of patients with varying degrees of acute limb ischemia.Conclusion The developed radionuclide patterns of acute ischemia in thrombosis of main arteries of the lower extremities allowed to determine the level of arterial occlusion and the degree of acute ischemia, identify the areas of lack of blood supply and necrosis with no clinical signs at an early stage of formation and optimize the treatment strategy.